Medieval Religious Rationalities : A Weberian Analysis / [electronic resource] - d'Avray, D. L. (Cambridge : Cambridge University Press, 2010)
Inspired by the social theories of Max Weber, David d'Avray asks in what senses medieval religion was rational and, in doing so, proposes a new approach to the study of the medieval past. Applying ideas developed in his companion volume on Rationalities in History, he explores how values, instrumental calculation, legal formality and substantive rationality interact and the ways in which medieval beliefs were strengthened by their mutual connections, by experience, and by mental images. He sheds new light on key themes and figures in medieval religion ranging from conversion, miracles and the ideas of Bernard of Clairvaux to Trinitarianism, papal government and Francis of Assisi's charismatic authority. This book shows how values and instrumental calculation affect each other in practice and demonstrates the ways in which the application of social theory can be used to generate fresh empirical research as well as new interpretative insights.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Values; Sociology